Industrial synthesis preparation method of potassium-sodium niobate-based piezoelectric ceramic element
Through the industrial synthesis and preparation method, the coordinated doping and modification of KNN-based piezoelectric ceramics is solved, and the problems of low production efficiency, poor performance consistency and safety hazards in the prior art are realized, and the mass production of KNN-based piezoelectric ceramic components with high density and excellent piezoelectric performance are realized.
Patent Information
- Application Number
- CN202510031112.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The existing preparation methods of KNN-based piezoelectric ceramics remain at the laboratory level, with low production efficiency and poor performance consistency. Due to the use of anhydrous ethanol, it leads to high production costs and safety risks, making it difficult to achieve mass production.
The industrial synthesis preparation method is adopted, including wet ball milling, high temperature synthesis, spray drying, low pressure pressing, isostatic pressure forming and high temperature sintering, and KNN-based piezoelectric ceramic components with high density and excellent piezoelectric properties are prepared by introducing MnO2, Li+ and Sb5+ for coordinated doping and modification.
The mass production of KNN-based piezoelectric ceramics is realized, which improves density and piezoelectric performance, reduces production costs and safety risks, and is suitable for large-scale production and high-power emission piezoelectric transducers.
Smart Images

Figure CN119822826A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric ceramics, and in particular to an industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element. Background Art
[0002] Piezoelectric ceramic materials can realize the mutual conversion between electrical energy and mechanical energy, and have the characteristics of simple preparation process and low production cost. They are widely used in transducers, sensors, actuators and other fields. At present, the lead (Pb) content of lead zirconate titanate (PZT) piezoelectric ceramics widely used on the market is as high as more than 60%. During the manufacturing, use and waste disposal process, it will cause irreversible harm to human health and the ecological environment. Therefore, the development of a lead-free piezoelectric ceramic that can replace PZT has become a research hotspot in the international community in recent years. In the lead-free piezoelectric ceramic system, potassium sodium niobate (KNN)-based lead-free piezoelectric ceramics are widely used in the market. 33 As high as 680pC / N, it is better than the commercial PZT-5H piezoelectric ceramics and is one of the most likely systems to replace lead-based piezoelectric ceramics.
[0003] The Chinese patent with publication number CN115572166A discloses that (0.96-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O 3 -x(Bi 0.5 R 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 HkDJ 3 Base piezoelectric ceramic, d 33 =535±20pC / N, mechanical quality factor Q m =34, plane electromechanical coupling coefficient k P =55%, dielectric loss tanδ=0.04, Curie temperature T C =221℃; in this method, anhydrous ethanol is used as the ball milling medium twice. The Chinese patent with publication number CN105198417B discloses the preparation of (lx)K by the planetary ball milling method commonly used in the laboratory. 0.48 Na 0.52 Nb 0.95 Sb 0.05 O 3 -x(Bi 0.5 Na 0.5 ) l-y (Li 0.5 Ce 0.5 ) y ZrO3 Base piezoelectric ceramics, its d 33 =400~485pC / N, plane electromechanical coupling coefficient k P =42~52%; although this method does not specify the use of two consecutive anhydrous ethanol as the ball milling medium, it should be so in practice; and this preparation method is only suitable for laboratory-level sample preparation and does not have the characteristics of mass production. The Chinese patent with publication number CN115321980B discloses the use of laboratory planetary ball milling method to prepare two powder particle sizes (lx)K by traditional ball milling and high-energy ball milling 0.48 Na 0.52 Nb 0.95 Sb 0.05 O 3 -x(Bi 0.5 Na 0.5 ) l-y (Li 0.5 Ce 0.5 ) y ZrO 3 The piezoelectric ceramic powder is mixed to prepare the piezoelectric ceramic. By constructing a hierarchical domain structure between grains and using the pinning effect of the grain boundary on the domain wall, the d 33 and Q m , its 33 =300~386pC / N, mechanical quality factor Q m =90~141.
[0004] The preparation of the above-mentioned piezoelectric ceramics is carried out under laboratory conditions, that is, the production scale is small and the ingredients are of high precision. It is not difficult to see that the medium used in all processes involving ball milling and mixing is anhydrous ethanol. In industrial production, the use of anhydrous ethanol not only leads to high production costs, but also leads to safety hazards in the production process, and additional security mechanisms need to be added to protect civil defense safety. At present, deionized water is used in the production and preparation process of traditional PZT ceramics, which has low production costs and high safety factors. Therefore, how to reduce or even avoid the use of anhydrous ethanol in the production of KNN-based ceramics, and to achieve its controllable batch preparation, is the basic prerequisite for realizing the replacement of PZT ceramics with KNN-based ceramics.
[0005] The Chinese patent publication number CN113666744A discloses a method for preparing a KNN-based lead-free piezoelectric ceramic having a composition gradient by a tape casting method. 33 The Chinese patent with publication number CN114262228A discloses adding Sb and (Bi0.5Na0.5)ZrO3 to the KNN system. 33 It has been increased to 455pC / N. It is usually formed by regulating the sintering process or element doping to form oxygen vacancies, thereby pinning the domain wall, inhibiting domain wall movement, and improving the Q of piezoelectric ceramics.m However, the formation of oxygen vacancies will lead to an increase in high-temperature conductivity, d 33 For example, the Chinese patent with publication number CN114276138A discloses a method for adjusting the oxygen vacancy concentration in KNN piezoelectric ceramics by combining hot pressing sintering with annealing process, thereby adjusting the hardening of the piezoelectric ceramics. m =250~280,d 33 The Chinese patent with the authorization announcement number CN100408509C discloses that adding CuO to the KNN system can increase the Q of the material. m Adjustable between 100~1600, d 33 Between 90 and 120. The Chinese patent with the authorization announcement number CN106588007B discloses a class of chemical formulas of 0.956 (0.988-x) (K 0.3 7Na 0.63 ) 0.86 Ca 0.04 Li 0.02 Nb 0.85 O 3 -0.044(0.988-x)K 0.85 Ti 0.85 Nb 1.15 O 5 -xBaSnO 3 -yMnO-zCeO lead-free piezoelectric ceramics, the Q m Between 112 and 137, d 33 Less than 264pC / N.
[0006] The d of pure KNN ceramics prepared by ordinary sintering process 33 It is only about 80pC / N, which cannot meet the requirements of underwater acoustic transducers. Through element doping and modification, the piezoelectric properties of KNN-based piezoelectric ceramics have been rapidly improved in recent years, up to 550pC / N. In addition, while the piezoelectric performance has been improved, its Curie temperature has also dropped sharply, thus limiting the temperature application range of the piezoelectric material in the equipment and use process. Due to the elemental characteristics of KNN-based ceramics (K / Na is easily soluble in water, and an organic solvent is required as a mixing medium), it is difficult to prepare it using conventional industrial methods.
[0007] In summary, KNN-based piezoelectric ceramics have been used in traditional civilian fields, indicating that the material has practical value, but the preparation method is still at the stage of laboratory production methods, with low production efficiency and poor performance consistency. Due to the limitations of the production method, only less than 100g of raw materials can be produced each time. In addition, since the laboratory still uses manual plasticization and granulation methods for powders, the powder has poor fluidity and cannot form larger piezoelectric components. In addition, by using the organic solvent casting method, KNN-based piezoelectric ceramics are also used in some acoustic and electrical devices, such as buzzers, atomizers and other small household appliances. However, the use of a large amount of organic solvents in this method is not only harmful to the human body, but also leads to a low density of ceramic components, which cannot meet the use of high-power transmitting transducers and needs to be improved. Summary of the invention
[0008] The problem to be solved by the present invention is to provide an industrial synthesis preparation method for potassium sodium niobate-based piezoelectric ceramic elements in view of the above-mentioned deficiencies in the prior art, which improves the piezoelectric properties such as density and piezoelectric constant of KNN-based piezoelectric ceramics, has good fluidity and plasticity, reduces production risks, and is suitable for mass production.
[0009] The above-mentioned object of the present invention is achieved through the following technical solutions: An industrial synthesis preparation method of potassium sodium niobate-based piezoelectric ceramic elements comprises the following steps: S1 raw material Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , Sb 2 O 3 、BaCO 3 、ZrO 2 、Bi 2 O 3 、MnO 2 According to the stoichiometric formula, 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.5mol%MnO 2 After weighing, the mixture is subjected to wet ball milling and drying in sequence to obtain ball milled powder; S2: in a closed environment, the ball-milled powder undergoes a high-temperature synthesis reaction, and after the reaction is completed, the powder is post-processed to obtain a reaction powder; S3: wet ball milling the reaction powder, adding a binder, a dispersant and a defoamer, stirring and mixing the mixture, and spray drying the mixture to obtain a piezoelectric ceramic powder; S4: subjecting the piezoelectric ceramic powder to low-pressure pressing and isostatic hydroforming in sequence, and then subjecting it to high-temperature plastic discharge to obtain a formed body; S5: in a closed oxidation space, subjecting the formed green body to a high temperature sintering treatment, and after the sintering is completed, subjecting the green body to a post-treatment to obtain a piezoelectric ceramic component; S6: After the piezoelectric ceramic piece is processed into a predetermined shape, it is subjected to upper electrode and silicone oil polarization treatment in sequence to obtain a piezoelectric ceramic element.
[0010] Furthermore, in S1, the wet ball milling uses a drum ball mill, the ball milling medium is zirconium balls, the liquid medium is anhydrous ethanol, the raw materials are pre-dried at 120-150°C for 10-40h, the weight ratio of the raw materials, zirconium balls and anhydrous ethanol is 1.0:3.0-4.0:1.5-2.5, the ball milling time is 10-30h, the drying temperature is 80-90°C, and the drying time is 5-10h. Among them, the raw material pre-drying is to remove free water in the raw material and crystal water in the carbonate. The wet ball milling process determines the optimal ball milling speed according to the drum diameter. After the slurry is discharged, the slurry is poured into the oven tray for drying. The oven needs to be equipped with a strong blast exhaust device to remove the volatilized ethanol in time.
[0011] Furthermore, in S2, the high temperature synthesis reaction is first carried out at 600-700°C for 0.5-2.0h, then the temperature is raised to 820-880°C for 2.0-4.0h, and after the reaction is completed, the reaction mixture is crushed and sieved to obtain a reaction powder.
[0012] Further, in S3, the wet ball milling adopts a stirred ball mill, the ball milling medium is zirconium balls, the liquid medium is deionized water, the weight ratio of the reaction powder, zirconium balls and deionized water is 1.0:3.0~4.0:1.2~1.8, the ball milling time is 2~8h, the ball milling speed is 50~150r / min, and the diameter of the ball milled slurry is D 50 =0.8~2.0μm.
[0013] Furthermore, in S3, the binder is a 7wt% PVA solution, the dispersant is Hydrodisper A160, and the defoamer is n-octanol; 4000-5000mL of the binder, 180-230mL of the dispersant, and 10-15mL of the defoamer are added to every 30kg of the ball mill slurry. The piezoelectric ceramic powder thus obtained has good fluidity and plasticity, and can be formed into piezoelectric elements of various specifications and sizes, such as discs, rings, round tubes, strips, etc.
[0014] Alternatively, in S3, the binder is PVA, phenolic resin, sodium carboxymethyl cellulose (CMC), methyl cellulose, alginate, polyacrylamide, PVP or HPMC, the dispersant is polyethylene glycol, corn oil, glycerol, polyacrylic acid salt or polyethyleneimine, and the defoamer is silicone defoamer, polyether defoamer or mineral oil defoamer.
[0015] Furthermore, in S4, the pressure of the low pressure pressing is 0.9-1.2 T / cm 2 , time is 10~30s, the pressure of isostatic hydroforming is 160~200MPa, the time is 25~35s, the temperature of high-temperature plastic discharge is 750~850℃, the time is 2~5h, and the size of the molded blank is Ф33´4.5~5.0mm.
[0016] Furthermore, in S5, a plurality of molded green bodies are arranged in the closed oxidation space, the ratio of these molded green bodies filling the closed sintering space is 30-50%, and piezoelectric ceramic powder is evenly spread between the surfaces of these molded green bodies and the closed oxidation space.
[0017] Furthermore, in S5, the high temperature sintering is performed at a temperature of 1050-1140° C. and a time of 2-4 hours.
[0018] Furthermore, in S6, after the piezoelectric ceramic component is processed into a size of Ф25´2.0mm, silver electrodes are printed on the surfaces of both sides of the piezoelectric ceramic component using a screen printing process. After the silver electrodes are dried, they are placed in a heating furnace, heated to 700~800℃ and kept warm for 25~35min, and then naturally cooled to room temperature to complete the electrode application process.
[0019] Furthermore, in S6, the piezoelectric ceramic element passing through the upper electrode is placed in silicone oil at 60-120° C., a DC electric field of 2.5-3.5 kV / mm is applied, and maintained for 10-20 minutes for polarization. After the polarization is completed, the silicone oil on the surface of the piezoelectric ceramic element is cleaned and removed.
[0020] In summary, the beneficial technical effects of the present invention are: 1. The KNN-based piezoelectric ceramic element of the present invention is based on the potassium sodium niobate-barium zirconate-sodium bismuth zirconate system, rationally controls the proportion of the three components, and introduces MnO 2 , Li + With Sb 5+ Through collaborative doping and modification, the dielectric constant ε can be obtained r ≥1850,d 33 ≥286pC / N, planar electromechanical coupling coefficient k p ≥0.47, Mechanical quality factor Q m ≥39, dielectric loss tanδ≤3.23%, density ρ =4.56g / cm 3 Piezoelectric ceramics; 2. The present invention can realize the mass production of KNN-based piezoelectric ceramics through large-scale exothermic drum wet ball milling, and with the aid of spray granulation technology, can obtain KNN-based piezoelectric ceramic powder with good fluidity and plasticity, so that it can adapt to the molding of multi-specification and large-size piezoelectric elements. The density of the piezoelectric ceramics prepared in this way is greatly improved compared with the piezoelectric ceramics formed by the casting method, and the KNN piezoelectric ceramics have extremely high piezoelectricity and higher density, so it is expected that the material can be used in high-power transmitting piezoelectric transducers; 3. The present invention can solve the problem of mass production of KNN-based piezoelectric ceramic powders, obtain piezoelectric ceramic powders with good fluidity and plasticity, and facilitate the molding of KNN-based piezoelectric ceramic components with multiple specifications and large sizes, such as piezoelectric ceramic discs, rings, round tubes, strips, etc.; 4. The second ball milling mixing of the present invention uses deionized water as the ball milling medium, which avoids the use of anhydrous ethanol, saves costs, and reduces safety hazards in the production process; 5. Due to the characteristics of dry pressing, the efficiency of the present invention is much higher than that of tape casting, and the density is also improved. In addition, the use of a large amount of organic solvents is reduced during the preparation of piezoelectric ceramic elements, which not only reduces the production cost, but also avoids the harm of organic solvents to operators during the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flow chart of the method provided in Example 1 of the present invention.
[0022] Figure 2 1 and 2 are the hysteresis loop and bipolar electrostrain curve of the piezoelectric ceramic element of Example 2 of the present invention.
[0023] Figure 3 This is a cross-sectional electron microscope image of the piezoelectric ceramic element of Example 2 of the present invention. DETAILED DESCRIPTION
[0024] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods.
[0025] Example 1: Reference Figure 1 , which is an industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, comprising the following steps: S1 raw material Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , Sb 2 O 3 、BaCO 3 、ZrO 2 、Bi 2 O 3 、MnO 2 According to the stoichiometric formula, 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.5mol%MnO 2 After weighing, the mixture is subjected to wet ball milling and drying in sequence to obtain ball milled powder; S2 In a closed environment, the ball-milled powder undergoes a high-temperature synthesis reaction, and after the reaction is completed, it is post-processed to obtain a reaction powder; S3: wet ball milling the reaction powder, adding a binder, a dispersant and a defoamer, stirring and mixing the mixture, and spray drying the mixture to obtain a piezoelectric ceramic powder; S4: the piezoelectric ceramic powder is subjected to low-pressure pressing and isostatic hydrostatic forming in sequence, and then subjected to high-temperature plastic discharge to obtain a formed body; S5: in a closed oxidation space, the formed green body is subjected to high temperature sintering treatment, and after the sintering is completed, the green body is subjected to post-treatment to obtain a piezoelectric ceramic component; S6 processes the piezoelectric ceramic piece into a predetermined shape, and then sequentially processes the upper electrode and silicone oil polarization to obtain a piezoelectric ceramic element.
[0026] Embodiment 2: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Embodiment 1 in that it includes the following steps: S1 raw material Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , Sb 2 O 3 、BaCO 3 、ZrO 2 、Bi 2 O 3 、MnO 2 According to the stoichiometric formula, 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.5mol%MnO 2 After weighing, based on 150 mol, a total of about 30 kg of raw materials were dried at 120 ° C for 10 h in advance, and then subjected to wet ball milling and drying treatments in sequence. The wet ball milling used a drum ball mill, the ball milling medium was zirconium balls, and the liquid medium was anhydrous ethanol. The weight ratio of the dried raw materials, zirconium balls, and anhydrous ethanol was 1.0:3.0:1.8. The ball milling time was 24 h, the drying temperature was 90 ° C, the drying time was 8 h, and the ball milling speed was 100 r / min to obtain ball milled powder. S2 is a ball-milled powder that is subjected to a high-temperature synthesis reaction in a closed environment, first reacting at 650°C for 0.5h, then heating to 850°C for 3.0h, and after the reaction is completed, crushing and screening to obtain a reaction powder; S3: The reaction powder is subjected to wet ball milling. The wet ball milling adopts a stirred ball mill. The ball milling medium is zirconium balls, the liquid medium is deionized water, the weight ratio of the reaction powder, zirconium balls and deionized water is 1.0:3.0:1.6, the ball milling time is 4h, the ball milling speed is 150r / min, and the ball mill slurry diameter is D 50 =1.2μm; prepare a PVA solution with a binder of 7wt%, a dispersant of Hydrodisper A160, and a defoamer of n-octanol; add 4200mL of binder, 180mL of dispersant, and 15mL of defoamer to every 30kg of ball mill slurry, stir and mix thoroughly, and then spray dry to obtain piezoelectric ceramic powder; S4 processes the piezoelectric ceramic powder by low-pressure pressing and isostatic hydrostatic pressing in sequence. The pressure of low-pressure pressing is 1.2T / cm2 , time is 30s, isostatic hydroforming pressure is 160MPa, time is 30s, and then high temperature plastic discharge, high temperature plastic discharge temperature is 780℃, time is 2h, to obtain Ф33´4.5mm molded green body; S5: multiple formed green bodies are arranged in the closed oxidation space, the proportion of these formed green bodies filling the closed sintering space is 40%, and piezoelectric ceramic powder is evenly laid between the surfaces of these formed green bodies and the closed oxidation space, and the formed green bodies are subjected to high-temperature sintering treatment, the high-temperature sintering temperature is 1120°C, the time is 3h, and after the sintering is completed, the piezoelectric ceramic parts are obtained by post-processing; S6 processes the piezoelectric ceramic component into a size of Ф25´2.0mm, and then uses a screen printing process to print silver electrodes on the surfaces of both sides of the piezoelectric ceramic component. After the silver electrodes are dried, they are placed in a heating furnace, heated to 750°C and kept warm for 30 minutes, and then naturally cooled to room temperature to complete the electrode process. The piezoelectric ceramic element that has passed the upper electrode is placed in 90°C silicone oil, and a DC electric field of 3.0kv / mm is applied and maintained for 15 minutes for polarization. After the polarization is completed, the silicone oil on the surface of the piezoelectric ceramic element is cleaned and removed to obtain a piezoelectric ceramic element.
[0027] Embodiment 3: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Embodiment 1 in that it includes the following steps: S1 raw material Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , Sb 2 O 3 、BaCO 3 、ZrO 2 、Bi 2 O 3 、MnO 2 According to the stoichiometric formula, 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.5mol%MnO 2After weighing, it was dried at 120°C for 10 hours in advance, and then subjected to wet ball milling and drying treatments in sequence. The wet ball milling used a drum ball mill, the ball milling medium was zirconium balls, and the liquid medium was anhydrous ethanol. The weight ratio of the dried raw material, zirconium balls, and anhydrous ethanol was 1.0:3.0:1.5. The ball milling time was 10 hours, the drying temperature was 80°C, and the drying time was 5 hours to obtain ball milled powder. S2 is a closed environment where the ball-milled powder undergoes a high-temperature synthesis reaction, first at 600°C for 0.5h, then heated to 820°C for 2.0h. After the reaction is complete, the powder is crushed and sieved to obtain the reaction powder. S3: The reaction powder is subjected to wet ball milling. The wet ball milling adopts a stirred ball mill. The ball milling medium is zirconium balls, the liquid medium is deionized water, the weight ratio of the reaction powder, zirconium balls and deionized water is 1.0:3.0:1.2, the ball milling time is 2h, the ball milling speed is 50r / min, and the ball mill slurry diameter is D 50 =0.8μm; prepare a PVA solution with a binder of 7wt%, a dispersant of Hydrodisper A160, and a defoamer of n-octanol; add 4000mL of binder, 180mL of dispersant, and 10mL of defoamer to every 30kg of ball mill slurry, stir and mix thoroughly, and then spray dry to obtain piezoelectric ceramic powder; S4 processes the piezoelectric ceramic powder by low-pressure pressing and isostatic hydrostatic pressing in sequence. The pressure of low-pressure pressing is 0.9T / cm 2 , time is 10s, isostatic hydroforming pressure is 160MPa, time is 25s, and then high temperature plastic discharge, high temperature plastic discharge temperature is 750℃, time is 2h, to obtain Ф33´4.5mm molded green body; S5: multiple formed green bodies are arranged in the closed oxidation space, the proportion of these formed green bodies filling the closed sintering space is 30%, and piezoelectric ceramic powder is evenly laid between the surfaces of these formed green bodies and the closed oxidation space, and the formed green bodies are subjected to high-temperature sintering treatment, the high-temperature sintering temperature is 1050°C, the time is 2h, and after the sintering is completed, the piezoelectric ceramic pieces are obtained by post-processing; S6 processes the piezoelectric ceramic component into a size of Ф25´2.0mm, and then uses a screen printing process to print silver electrodes on the surfaces of both sides of the piezoelectric ceramic component. After the silver electrodes are dried, they are placed in a heating furnace, heated to 700°C and kept warm for 25 minutes, and then naturally cooled to room temperature to complete the electrode process. The piezoelectric ceramic element that has passed the upper electrode is placed in 60°C silicone oil, and a direct current electric field of 2.5kv / mm is applied and maintained for 10 minutes for polarization. After the polarization is completed, the silicone oil on the surface of the piezoelectric ceramic element is cleaned and removed to obtain a piezoelectric ceramic element.
[0028] Embodiment 4: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Embodiment 1 in that it includes the following steps: S1 raw material Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , Sb 2 O 3 、BaCO 3 、ZrO 2 、Bi 2 O 3 、MnO 2 According to the stoichiometric formula, 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.5mol%MnO 2 After weighing, it was dried at 150°C for 40 hours in advance, and then subjected to wet ball milling mixing and drying treatments in sequence. The wet ball milling used a drum ball mill, the ball milling medium was zirconium balls, and the liquid medium was anhydrous ethanol. The weight ratio of the dried raw material, zirconium balls, and anhydrous ethanol was 1.0:4.0:2.5. The ball milling time was 30 hours, the drying temperature was 90°C, and the drying time was 10 hours to obtain ball milled powder. S2 is a closed environment where the ball-milled powder undergoes a high-temperature synthesis reaction, first at 700°C for 2.0h, then heated to 880°C for 4.0h. After the reaction is complete, the powder is crushed and sieved to obtain the reaction powder. S3: The reaction powder is subjected to wet ball milling. The wet ball milling adopts a stirred ball mill. The ball milling medium is zirconium balls, the liquid medium is deionized water, the weight ratio of the reaction powder, zirconium balls and deionized water is 1.0:4.0:1.8, the ball milling time is 8h, the ball milling speed is 150r / min, and the ball mill slurry diameter is D 50 =2.0μm; prepare a PVA solution with a binder of 7wt%, a dispersant of Hydrodisper A160, and a defoamer of n-octanol; add 5000mL of binder, 230mL of dispersant, and 15mL of defoamer to every 30kg of ball mill slurry, stir and mix thoroughly, and then spray dry to obtain piezoelectric ceramic powder; S4 processes the piezoelectric ceramic powder by low-pressure pressing and isostatic hydrostatic pressing in sequence. The pressure of low-pressure pressing is 1.2T / cm 2 , time is 30s, isostatic hydroforming pressure is 200MPa, time is 35s, and then high temperature plastic discharge, high temperature plastic discharge temperature is 850℃, time is 5h, to obtain Ф33´5.0mm molded green body; S5: multiple formed green bodies are arranged in the closed oxidation space, the proportion of these formed green bodies filling the closed sintering space is 50%, and piezoelectric ceramic powder is evenly laid between the surfaces of these formed green bodies and the closed oxidation space, and the formed green bodies are subjected to high-temperature sintering treatment, the high-temperature sintering temperature is 1140°C, the time is 4h, and after the sintering is completed, the piezoelectric ceramic pieces are obtained by post-processing; S6 processes the piezoelectric ceramic component into a size of Ф25´2.0mm, and then uses a screen printing process to print silver electrodes on the surfaces of both sides of the piezoelectric ceramic component. After the silver electrodes are dried, they are placed in a heating furnace, heated to 800°C and kept warm for 35 minutes, and then naturally cooled to room temperature to complete the electrode process. The piezoelectric ceramic element that has passed the upper electrode is placed in 120°C silicone oil, and a DC electric field of 3.5kv / mm is applied and maintained for 20 minutes for polarization. After the polarization is completed, the silicone oil on the surface of the piezoelectric ceramic element is cleaned and removed to obtain a piezoelectric ceramic element.
[0029] Comparative Example 1: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Example 2 in that, in S1, according to the stoichiometric formula 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.2mol%MnO 2 Weighing.
[0030] Comparative Example 2: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Example 2 in that, in S1, according to the stoichiometric formula 0.94 (K 0.48 Na 0.50 Li 0 )(Nb 0.95 Sb 0.05 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO3 +0.5mol%MnO 2 Weighing.
[0031] Comparative Example 3: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Example 2 in that, in S1, according to the stoichiometric formula 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 1。00 Sb 0 ) 3 -0.03BaZrO 3 -0.02Bi 0.5 Na 0.5 ZrO 3 +0.5mol%MnO 2 Weighing.
[0032] Comparative Example 4: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Example 2 in that, in S1, according to the stoichiometric formula 0.96 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0BaZrO 3 -0.04Bi 0.5 Na 0.5 ZrO 3 Weighing.
[0033] Comparative Example 5: An industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element disclosed in the present invention, which is different from Example 2 in that, in S1, according to the stoichiometric formula 0.95 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 ) 3 -0.05BaZrO 3 -0Bi 0.5 Na 0.5 ZrO 3 +0.2mol%MnO 2 Weighing.
[0034] Experimental Example 1: The relationship between the hysteresis loop and the bipolar electrostrain of the piezoelectric ceramic element obtained in Example 2 was tested, and the cross-sectional microscopic electron microscope image was observed. The results are as follows: Figure 2~3 shown.
[0035] from Figure 2It can be seen that the piezoelectric ceramic element prepared by Example 2 has a saturated hysteresis loop and no obvious leakage current.
[0036] from Figure 3 It can be seen that the piezoelectric ceramic element prepared by Example 2 has closely packed microscopic grains, fewer pores, and higher density.
[0037] Experimental Example 2: The piezoelectric ceramic elements obtained in Examples 2 to 4 and Comparative Examples 1 to 5 were placed at room temperature for 24 hours, and their electrical properties were tested: the dielectric loss tanδ was measured using an HP4294 impedance analyzer, and the electromechanical coupling coefficient k was obtained by looking up the table and calculating. p , dielectric constant ε r and mechanical quality factor Q m , using ZJ-3A type d 33 Measuring instrument measures d 33 , the density ρ was measured by the Archimedean drainage method, and the results are shown in Table 1.
[0038] Table 1 Serial number <![CDATA[ε r ]]> tanδ(%) <![CDATA[k p ]]> <![CDATA[Q m ]]> <![CDATA[d 33 (pc•N-1)]]> <![CDATA[T C (℃)]]> <![CDATA[ρ(g / cm 3 )]]> Example 2 1850 3.23 0.47 39 286 255 4.56 Comparative Example 1 1920 3.56 0.48 36 312 248 4.52 Comparative Example 2 1850 3.23 0.47 39 286 255 4.56 Comparative Example 3 1850 3.23 0.47 39 286 255 4.56 Comparative Example 4 1850 3.23 0.47 39 286 255 4.56 Comparative Example 5 1850 3.23 0.47 39 286 255 4.56 It can be seen from Table 1 that in the comparative example, Li + , Sb 5+ 、BaZrO 3 、Bi 0.5 Na 0.5 ZrO 3 With MnO 2 The content of piezoelectric material has changed the corresponding electrical properties of the material. Overall, it still has high electrical properties and meets the application requirements of general piezoelectric devices.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An industrial synthesis method for preparing potassium sodium niobate-based piezoelectric ceramic elements, characterized in that: The following steps are included: S1 The raw materials Na2CO3, K2CO3, Li2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, MnO2 were mixed according to the stoichiometric formula 0.94 (K 0.48 Na 0.50 Li 0.02 )(Nb 0.95 Sb 0.05 )O3-0.03BaZrO3-0.02Bi 0.5 Na 0.5 After weighing, ZrO3+0.5mol%MnO2 was subjected to wet ball milling and drying in sequence to obtain ball milled powder; S2: in a closed environment, the ball-milled powder undergoes a high-temperature synthesis reaction, and after the reaction is completed, the powder is post-processed to obtain a reaction powder; S3: wet ball milling the reaction powder, adding a binder, a dispersant and a defoamer, stirring and mixing the mixture, and spray drying the mixture to obtain a piezoelectric ceramic powder; S4: subjecting the piezoelectric ceramic powder to low-pressure pressing and isostatic hydroforming in sequence, and then subjecting it to high-temperature plastic discharge to obtain a formed body; S5: in a closed oxidation space, subjecting the formed green body to a high temperature sintering treatment, and after the sintering is completed, subjecting the green body to a post-treatment to obtain a piezoelectric ceramic component; S6: After the piezoelectric ceramic piece is processed into a predetermined shape, it is subjected to upper electrode and silicone oil polarization treatment in sequence to obtain a piezoelectric ceramic element.
2. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In S1, the wet ball milling adopts a drum ball mill, the ball milling medium is zirconium balls, the liquid medium is anhydrous ethanol, the raw material is pre-dried at 120-150° C. for 10-40 hours, the weight ratio of the raw material, zirconium balls and anhydrous ethanol is 1.0:3.0-4.0:1.5-2.5, the ball milling time is 10-30 hours, the drying temperature is 80-90° C., and the drying time is 5-10 hours.
3. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In the S2, the high temperature synthesis reaction is first carried out at 600-700°C for 0.5-2.0h, and then the temperature is raised to 820-880°C for 2.0-4.0h. After the reaction is completed, the reaction is crushed and sieved to obtain a reaction powder.
4. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In S3, the wet ball milling adopts a stirred ball mill, the ball milling medium is zirconium balls, the liquid medium is deionized water, the weight ratio of the reaction powder, zirconium balls and deionized water is 1.0:3.0~4.0:1.2~1.8, the ball milling time is 2~8h, the ball milling speed is 50~150r / min, and the diameter of the ball milled slurry is D 50 =0.8~2.0μm.
5. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In S3, the binder is a 7 wt% PVA solution, the dispersant is Hydrodisper A160, and the defoamer is n-octanol; 4000-5000 mL of the binder, 180-230 mL of the dispersant, and 10-15 mL of the defoamer are added to every 30 kg of the ball mill slurry.
6. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In S4, the pressure of low pressure pressing is 0.9~1.2T / cm 2 , time is 10~30s, the pressure of isostatic hydroforming is 160~200MPa, the time is 25~35s, the temperature of high-temperature plastic discharge is 750~850℃, the time is 2~5h, and the size of the molded blank is Ф33´4.5~5.0mm.
7. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In the S5, a plurality of molded green bodies are arranged in the closed oxidation space, the ratio of these molded green bodies filling the closed sintering space is 30-50%, and piezoelectric ceramic powder is evenly spread between the surfaces of these molded green bodies and the closed oxidation space.
8. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In the step S5, the high temperature sintering is performed at a temperature of 1050-1140°C and a time of 2-4 hours.
9. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In the S6, after the piezoelectric ceramic component is processed into a size of Ф25´2.0mm, silver electrodes are printed on the surfaces of both sides of the piezoelectric ceramic component using a screen printing process. After the silver electrodes are dried, they are placed in a heating furnace, heated to 700~800℃ and kept warm for 25~35min, and then naturally cooled to room temperature to complete the electrode application process.
10. The industrial synthesis preparation method of a potassium sodium niobate-based piezoelectric ceramic element according to claim 1, characterized in that: In S6, the piezoelectric ceramic element passing through the upper electrode is placed in silicone oil at 60-120° C., a DC electric field of 2.5-3.5 kV / mm is applied, and maintained for 10-20 minutes for polarization. After the polarization is completed, the silicone oil on the surface of the piezoelectric ceramic element is cleaned and removed.
Citation Information
Patent Citations
Potassium sodium niobate based leadless piezoelectricity ceramic with high Qm and intermediate frequency resonator thereof
CN100408509C
A kind of preparation method of bismuth sodium zirconate lithium cerium doped potassium sodium niobate based ceramic material
CN105198417B
A high-quality lead-free piezoelectric ceramic
CN106588007B
Potassium-sodium niobate-based lead-free piezoelectric ceramic with gradient components and preparation method thereof
CN113666744A
Potassium-sodium niobate-based leadless piezoelectric ceramic as well as preparation method and application thereof
CN114262228A